Bottom-Up Construction of Complex Biomolecular Systems With Cell-Free Synthetic Biology - Laohakunakorn, Nadanai; Grasemann, Laura; Lavickova, Barbora; Michielin, Grégoire; Shahein, Amir; Swank, Zoe; Maerkl, Sebastian J. (Frontiers in Bioengineering and Biotechnology, 2020)
Cell-free systems offer a promising approach to engineer biology since their open nature allows for well-controlled and characterized reaction conditions. In this review, we discuss the history and recent developments in engineering recombinant and crude extract systems, as well as breakthroughs in enabling technologies, that have facilitated increased throughput, compartmentalization, and spatial control of cell-free protein synthesis reactions. Combined with a deeper understanding of the cell-free systems themselves, these advances improve our ability to address a range of scientific questions. By mastering control of the cell-free platform, we will be in a position to construct increasingly complex biomolecular systems, and approach natural biological complexity in a bottom-up manner.